1998
DOI: 10.1021/bi981551t
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Aα251 Fibrinogen:  The αC Domain Has a Role in Polymerization, Albeit More Subtle Than Anticipated from the Analogous Proteolytic Fragment X

Abstract: Numerous experiments have demonstrated that the C-terminal domain of the fibrinogen Aalpha-chain, the alphaC domain, has a role in polymerization. To further examine the role of this domain, we synthesized a recombinant fibrinogen, Aalpha251 fibrinogen, that lacks the alphaC domain. We examined thrombin-catalyzed fibrinopeptide release and found that the rate of FpB release from Aalpha251 fibrinogen was 2.5-fold slower than FpB release from normal fibrinogen, while the rate of FpA release was the same for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 52 publications
6
81
0
Order By: Relevance
“…Fibrinogen was labeled with 125 I using IODO-GEN (Thermo Scientific Pierce), dialyzed against PBS, and stored at Ϫ20°C. Recombinant normal (rFg; 340 kDa) and fibrinogen with the truncated ␣C regions (FgA␣251; 260 kDa) in which the A␣ chain is terminated at Thr-251, were produced as previously described (23). The protein concentration was determined by spectrophotometry at 280 nm using the extinction coefficient 1.51 at 1 mg/ml for hFg and 1.6 for rFg and FgA␣251.…”
Section: Methodsmentioning
confidence: 99%
“…Fibrinogen was labeled with 125 I using IODO-GEN (Thermo Scientific Pierce), dialyzed against PBS, and stored at Ϫ20°C. Recombinant normal (rFg; 340 kDa) and fibrinogen with the truncated ␣C regions (FgA␣251; 260 kDa) in which the A␣ chain is terminated at Thr-251, were produced as previously described (23). The protein concentration was determined by spectrophotometry at 280 nm using the extinction coefficient 1.51 at 1 mg/ml for hFg and 1.6 for rFg and FgA␣251.…”
Section: Methodsmentioning
confidence: 99%
“…The first, fibrinogen -251, described in 1998, contained a deletion of -chain amino acids 251-610 where most of cross-linking site are located [28]. Collet et al recently showed that in the presence of FXIII, clots made of fibrin -251 were denser, with the pore size decreasing by 1.8-fold, compared to wild-type fibrin [29].…”
Section: Fibrin - Chains Cross-linkingmentioning
confidence: 99%
“…We point out that although the snake venom enzyme Ancrod was used to avoid complicating the interpretation by even limited FpB release, the present data are quite similar to those we previously collected using thrombin and only a WA-MALS with a more limited angular range. 21,22 Further work with recombinant FG species with missing 48 or human/chicken hybrid 49 αC regions, and with either uncleavable FpB's or nonbinding B knobs/ unavailable b holes and thrombin as the enzyme, is planned. It should help to clarify the role played by the largely unstructured Aα chain appendages, which are also functionally important for FG adhesion, 50,51 …”
Section: ■ Conclusionmentioning
confidence: 99%